Механика 2 / ДО 2019 электронный курс - Горбенко М. В. Михаил Владимирович; Лазуркевич А. В. Артём Вячеславович; Коноваленко И. С. Иван Сергеевич; Черемискина М. С. Мария Сергеевна (Томск, TPU Moodle, 2021)
Заглавие с экрана